Development of information system based on mobile stock management in outlet. Issue 3 (March 2021) - Rahayu, S; Gunadhi, E; Ghipari, R; Fatimah, D D S
Abstract: Garut is a regency in West Java that has various potentials that can be developed. Now many industries have been established. The food or culinary industry is one of the special characteristics of Garut Regency. One of them is a company engaged in the dodol food industry, PT. Herlinah Cipta Pratama, which has several outlets in terms of consignment delivery of dodol. Problems for the delivery of dodol occur because of the shipping process by PT. Herlinah Cipta Pratama which does not match the stock management at the outlet. Therefore, it will need a system that can manage dodol stock in outlets that can be set by PT. Herlinah Cipta Pratama. With the Unified Software Development Process design method with the stages of Requirement, Analysis, Design and Implementation. The results of this study in the form of dodol stock information system design at PT. Herlinah is expected to be able to help the problems in the stock management with the aim that both parties can know the consignment process.